Systematic Pharmacological Strategies to Explore the Regulatory Mechanism of Ma Xing Shi Gan Decoction on COVID-19 - Zhang Shi-Ying; Li Ling; Zhang Ning; Xia Hong-Tao; Lu Fang-Guo; Li Wei-Qing (KeAi Communications Co., Ltd., 2020)
Objective: To use systematic pharmacological strategies to explore the regulatory mechanisms of Ma Xing Shi Gan Decoction (MXSGD) against the coronavirus disease 2019 (COVID-19). Methods: Data on the compounds and targets of MXSGD were collected from the Traditional Chinese Medicene Systems Parmacology Database and Analysis Platform (TCMSP) and TCM Databases@Taiwan. Data on ACE2-related targets and the protein-protein interaction (PPI) were collected from the String database. The Cytoscape 3.7.2 was used to construct and analyze the networks. The DAVID platform was used for Gene Ontology (GO) and pathway enrichment analyses. Results: Data on 272 MXSGD targets and 21 SARS-CoV-2 potential targets were collected. Four networks were constructed and analyzed based on the data: (1) compound-target network of MXSGD; (2) MXSGD-SARS-CoV-2-PPI network; (3) cluster of MXSGD-SARS-CoV-2-PPI network; (4) Herb-Pathway-Target network. The core targets included AKT1, MAPK3, IL-6, TP53, VEGFA, TNF, CASP3, EGFR, EGF and MAPK1. The antiviral biological processes were inflammatory responses (inflammatory cells, inflammatory cytokines and their signaling pathways), immune responses (T cells, monocytes, B cells and other immune cells), immune factors (IFN-γ, TNF-α and so on), virus defense, humoral immunity and mucosal innate immune response. The antivirus-related signaling pathways included TNF, NOD-like receptor, FoxO, PI3K-AKT and Toll-like receptor signaling pathways. Conclusions: MXSGD can control disease progression by regulating multiple compounds and targets; it can reduce inflammation and balance immunity by regulating several proteins that interact with ACE2 and signaling pathways closely related to disease development.